PROBLEMATIC ASPECTS OF THE CONSUMER PROTECTION ACT 28 OF 2008 IN RELATION TO PROPERTY TRANSACTIONS: LINKED TRANSACTIONS, FIXED-TERM CONTRACTS AND UNSIGNED SALE AGREEMENTS - Henk Delport (Obiter, 2014)
The article examines whether and to what extent sections 13(1), 14 and 50(2)(a) of the Consumer Protection Act 68 of 2008 apply to transactions relating to immovable property. Section 13(1) concerns linked agreements (also known as “tying arrangements”), section 14 deals with fixed-term contracts while section 50(2)(a) relates to unsigned written agreements. It is submitted that section 13(1) applies to plot-and-plan transactions entered into by property developers, as well as leases of immovable property where the lessee is obligated to enter into agreements with third parties such as security companies or garden-maintenance services. There is considerable confusion in the property industry whether section 14 applies to estate agency sole mandates and leases of immovable property where one or both parties are a natural person. The author submits that on a purposive interpretation of section 14 neither of these agreements is governed by the provision. Section 50(2)(a) conveys that when a consumer agreement is in writing either by reason of the provisions of the Act or voluntarily, the agreement is binding and enforceable whether or not the consumer signed the agreement. It is submitted that the provision does not apply to agreements of sale governed by the Alienation of Land Act 68 of 1981, the Share Blocks Control Act 59 of 1980, the Property Time-sharing Control Act 75 of 1983 and the Housing Development Schemes for Retired Persons Act 65 of 1988.